2021
DOI: 10.1021/acs.iecr.1c01592
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Carbon Dioxide Activation Pathway over Iron Oxide Catalysts: Effects of Potassium

Abstract: The activation of CO 2 to form CO, known as the reverse water−gas shift (RWGS) reaction, is an initial and essential step of numerous CO 2 hydrogenation reactions. However, the reaction is challenging, and the underlying CO 2 activation mechanism is usually overlooked when designing new heterogeneous catalysts. In this work, we investigate the effect of potassium, a common alkali metal promoter, on the iron oxide catalysts using a series of (quasi) in situ characterization techniques, kinetic analysis, and fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…37 Iron carbides are excluded from the reacted samples, which is also consistent with our previous Mossbauer spectrum analysis on the iron-based catalysts. 28 It is noted that the XRD signals for Al-, Cu-, and K-related phases are absent for the reaction-treated catalysts. Rietveld refinement of the crystal structures was performed using the program GSAS-II, with the results summarized in Table S4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Iron carbides are excluded from the reacted samples, which is also consistent with our previous Mossbauer spectrum analysis on the iron-based catalysts. 28 It is noted that the XRD signals for Al-, Cu-, and K-related phases are absent for the reaction-treated catalysts. Rietveld refinement of the crystal structures was performed using the program GSAS-II, with the results summarized in Table S4.…”
Section: Methodsmentioning
confidence: 99%
“…It is worthwhile to mention that AlFe has a 2-fold higher activity than the pure Fe 2 O 3 catalyst, which highlights the structural promotional effect of Al. 28 It is also noted, according to the literature, that the combination of Fe 2 O 3 and Cu yields much improved WGS/RWGS activities, attributed to their synergistic effect. 40 1KnCuAlFe exhibits much improved RWGS activity as compared with the nCuAlFe ones, and the addition of Cu still promotes the reaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches can be applied to modify the structure of metal oxides for the facile adsorption and dissociation of CO 2 molecules, mainly, through tailoring their physicochemical (e.g., improving surface basicity) [182,183] and electronic properties (e.g., doping and creating defect sites) [182].…”
Section: General Methods For Modifying Metal Oxide Surface Structure For Co 2 Transformationmentioning
confidence: 99%
“…The basic sites of metal oxide catalysts can be generated by pre-treatment with basic promoters such as La 2 O 3 , K 2 O, Na 2 O, and MgO [183]. Tian et al [182] reported that introducing potassium into iron oxide catalyst increased the surface basicity. Thus, alkali metals can be incorporated into the metal oxides to tune the concentration of surface basic sites.…”
Section: General Methods For Modifying Metal Oxide Surface Structure For Co 2 Transformationmentioning
confidence: 99%